Veiklos matavimas: bandymas Vilniaus universiteto bibliotekoje - Rudžionienė, Jurgita (Information & Media, 1996)
One of several methods for better utilization of changes that strongly affect the library performance is the regular measurement of library performance. Academic libraries all over the world recognize the need for effective management tools. This interest in management in some countries has become almost a routine, while in others it is just beginning. Evaluation of library services in Lithuania is a relatively recent phenomenon.So as a part of the Swedish-Baltic Library Management Project an attempt to do an investigation of library performance measurement at the Vilnius University Library was made. As methodical basis of the investigation served for us the Manual Measuring Quality: International Guidelines for Performance Measurement in Academic Libraries, drawn up by the working group of the IFLA Section of University Libraries and other General Research Libraries in 1993, and consultations of our Swedish colleges from Stockholm University Library. For the library performance measurement we have chosen two indicators of the collection quality group of indicators:expert checklist (the measurement of the ratio of items in the collection as listed in bibliographies);collection use (the measurement of collection use; was applied only partly).This choice was determined by the demand to find out how library collections meet contemporary topicality requirements to the literature on certain subject. Libraries in which performance was measured are:Freedom Forum Journalism Library (FFJL), Institute of Journalism, Faculty of Communication, Vilnius University;Library of the Institute of International Relations and Political Science (LIIRPS), Vilnius University.Measuring library performance in two libraries of VUL as described in this article is only one level of performance control. This was the first step made towards an extensive and comprehensive library performance evaluation program.